2008
DOI: 10.1111/j.1365-3024.2008.01027.x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of GPI anchor moiety on the immunogenicity of DNA plasmids encoding the 19‐kDa C‐terminal portion of Plasmodium falciparum MSP‐1

Abstract: SUMMARY The glycosylphosphatidylinositol (GPI)‐anchored Plasmodium falciparum merozoite surface protein 1 (MSP‐1) is a widely studied malaria vaccine candidate. The C‐terminal 19‐kDa portion of MSP‐1 (MSP‐119) is of particular interest because this polypeptide moiety remains bound to the parasite even after erythrocyte invasion, while the remainder of MSP‐1 is shed during invasion. Studies have shown that antibodies against MSP‐119 inhibit merozoite invasion of erythrocytes efficiently, and that MSP‐119 produ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
6
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 27 publications
(105 reference statements)
1
6
0
Order By: Relevance
“…Immunization with recombinant PvTRAg-26 resulted in a high level of IgG antibody response in mice, in which IgG1 subclass was predominant, followed by IgG2a. Similar results were also seen in the studies of mice with other malaria vaccine candidates, such as PvMSP1 19 , PfMSP1 19 , and PvMSP9 (34)(35)(36). The IgG1 and IgG3 antibodies are non-cytophilic and responsible for Th2-biased response (37), while the IgG2a and IgG2b are cytophilic and link to Th1 response in mice.…”
Section: Discussionsupporting
confidence: 80%
“…Immunization with recombinant PvTRAg-26 resulted in a high level of IgG antibody response in mice, in which IgG1 subclass was predominant, followed by IgG2a. Similar results were also seen in the studies of mice with other malaria vaccine candidates, such as PvMSP1 19 , PfMSP1 19 , and PvMSP9 (34)(35)(36). The IgG1 and IgG3 antibodies are non-cytophilic and responsible for Th2-biased response (37), while the IgG2a and IgG2b are cytophilic and link to Th1 response in mice.…”
Section: Discussionsupporting
confidence: 80%
“…Antibody to the C-terminal region of this protein (MSP-1 19 ) has been shown to block parasite invasion in vitro (11)(12)(13). Earlier studies have demonstrated that immune responses elicited separately by PvMSP-1 19 (14,15) or PfMSP-1 19 (16)(17)(18) antigens in mice induced high levels of IgG1 antibodies followed by IgG2a and IgG2b as well as a high level of IFN-c. A partial protection was also observed after immunization of nonhuman primates with PfMSP-1 19 (5) and PvMSP-1 19 (19). In addition, several studies on naturally acquired immunity showed that the antibodies (IgG1 and IgG3) against this antigen are correlated with protection (20)(21)(22)(23).…”
Section: Introductionmentioning
confidence: 99%
“…The five recombinant proteins induced similar antibody patterns, being IgG1, IgG2a and IgG2b the most predominant. Previous studies have shown that immune responses induced by PvMSP1 19 antigens [35,36] or PfMSP1 19 [37,38,39] in mice confer high levels of IgG1 subclasses, followed by IgG2a and IgG2b. Others authors also found similar results with recombinant proteins derived from PvMSP9 [40].…”
Section: Discussionmentioning
confidence: 99%